Meditasi Cinta Kasih untuk Mengembangkan Kepedulian dan Percaya Diri - Joni Pranata; Hadion Wijoyo (Jurnal Maitreyawira, 2020)
The practice of loving kindness meditation aims to describe a sense of care and confidence in students. To achieve maximum results, of course, it takes meditation habituation, techniques and meditation objects at the Buddhist Taman Lumbini Sunday school. Meditation practice is a program originating from the chairman of SMB Taman Lumbini and the coach's brother; practice loving-kindness meditation regularly every Sunday; brother coaches become direct guides; meditation practice is done in class, chedi, Dhamma classrooms, halls, or Sunday school grounds; students concentrate on the object of loving-kindness meditation or listen to positive sentences, intermediate meditation using audio meditation guides, bells, slide pictures. The object of meditation is breathing and then emphasizing the object of loving kindness. To be able to develop love, we must be able to feel the love within ourselves just being radiated out, with love it will make someone have a high sense of care and confidence.